2019
DOI: 10.3126/janr.v2i1.26061
|View full text |Cite
|
Sign up to set email alerts
|

Economics of chhari and marketable-size carps in Bara, Nepal

Abstract: A study was conducted to analyze the economics of production of chhari and marketable-size carps in Bara, Nepal. All total 90 farmers; 45 chhari producing and 45 marketable-size carps producing farmers were selected randomly and surveyed through pre-tested semi-structured interview based schedule on the month of March, 2019. Data was entered and analyzed using STATA 12.1 and SPSS 25. Findings of the study revealed that the total cost of fish production per hectare of pond area was 971927 NRs/year. Chhari produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 6 publications
3
5
0
Order By: Relevance
“…A similar result was found (Adewuyi et al, 2010). The finding was aligned with, who reported a BCR of 1.97 for Chhari production and a BCR of 1.67 for Marketable-size carp in Bara district, Nepal (Adhikari et al, 2019). Further, a similar figure was reported in Sharma et.al.…”
Section: Benefit-cost Ratio Analysissupporting
confidence: 88%
“…A similar result was found (Adewuyi et al, 2010). The finding was aligned with, who reported a BCR of 1.97 for Chhari production and a BCR of 1.67 for Marketable-size carp in Bara district, Nepal (Adhikari et al, 2019). Further, a similar figure was reported in Sharma et.al.…”
Section: Benefit-cost Ratio Analysissupporting
confidence: 88%
“…The finding was aligned with Mkong, et al (2018), who reported cost of feed, cost of labor had positive and significant association with profitability of fish farming in Cameroon. A similar finding was found by Adhikari et al (2019), who reported positive and significant association of cost of feed, cost of labor to gross return from Chhari and marketable-size carp in Bara district. The finding was in line with Olagunju et al, (2007).…”
Section: Socio-economic Characteristics Of Respondentssupporting
confidence: 87%
“…The finding was aligned with the finding from Mkong, et al, (2018) where a unit increase in labor cost had led to a 0.49% increase in net profit from marine fishing. A similar finding was found by Adhikari et al, (2019), where he reported 100% increase in the cost of labor increase the income by 13.7% in Chhari and marketable-size carp. The finding was also in line with finding concluded by Singh., (2007), who reported unit increase in the cost of hired labor increase the fish production by 0.916 in West Tripura district of Tripura.…”
Section: Socio-economic Characteristics Of Respondentssupporting
confidence: 81%
See 2 more Smart Citations